(untitled) (Pubmet, 2023)
Citizen science, as part of open science, holds significant importance for its participants, including citizen scientists and professional scientists who engage in collaborative scientific research (Booney et al., 2009). However, the benefits that organizers of citizen science gain are rarely emphasized. These organizers can include governmental organizations, non-governmental organizations, corporations, universities (Walker et al., 2016), as well as institutions such as libraries. Citizen science is important for libraries because it increases civic and research interests, scientific publishing, and scientific progress (Trouille, Lintott, and Fortson, 2019). Additionally, it helps libraries attract new users, enhance social cohesion, and improve the perception of library’s social value (Cigarini et al., 2021). With the help of citizen science, libraries can enrich their collections and make them more accessible (Ignat et al., 2018), and librarians can develop new competencies. The presentation aims to provide a comprehensive understanding of the specific ways in which citizen science can benefit libraries and how libraries can effectively utilize citizen science to achieve their goals. Therefore, the benefits of citizen science for libraries will be discussed in detail, with examples and practical insights provided to illustrate their potential impact. The presentation will include an analysis and experience of the National and University Library in Zagreb with carrying out citizen science activities and the advantages this institution had for librarian education. It will highlight the essential role of libraries as implementers of citizen science activities and the impact of such activities on the positioning of libraries in local society and the scientific community.